THE EFFECT OF CRUDE EXTRACT ALGINATE Sargassum crassifolium POWDER FOR CHOLESTEROL TOTAL LEVEL ON RATS (Rattus norvegicus) - Nandarningtiyas Laras Pratiwi (Journal of Innovation and Applied Technology, 2016)
Dietary fiber in alginate of Sargassum crassifolium is one way to reduce high cholesterol level. The purpose of this researchshowedthe effect of crude extract alginat powder for reduced lipid profile on rats.The crude extract alginate powder was given orally to hyperlipidemia rats at the doses level of 100 mg/kg, 200 mg/kg, 400 mg/kg, and 800 mg/kg body weight for 20 days. The method of profile lipid analyse used CHOD PAP and GPO PAP.  The result showed that the growth of weight body and feed consumption did not give a significant effect (p>0.05), in the other hand it has a significant effect (p<0.05) on the cholesterol level , trygliseride level, HDL level, LDL level, VLDL level and cholesterol level in feses. For 20 dayscrude extrac alginate Sargassum crassifolium reduced cholesterol total level for 800 mg/ dl body weight as much as 50,43%, 200 mg/dl to 40,45%, 100 mg/kg to 34,73% and control (+) which used simvastatin to 42,23%.